Scholarship Policies of International Students in Chinese Universities: A Brand Perception Perspective - Wang, Nuo (Frontiers in Psychology, 2022)
China has carried out a series of higher education reforms in the past decades. One of the most important parts of the reforms is the internationalization progress of Chinese universities. Despite being a developing country, China offers globally competitive scholarships to international students. However, surprisingly, little research has touched on how international students view China’s high scholarship policies, leaving an important and intriguing question underexplored. Therefore, this paper attempts to fill the literature gap by investigating international students’ brand perceptions of Chinese universities that provide high scholarships. Moreover, we reveal the process of their judgments through identifying the mediating role of perceived quality. A set of two experimental studies provide convergent support for these propositions. Theoretically, the findings of this paper contribute to the literature on higher education reforms, scholarship policies, and branding. In terms of practice, the research results offer implications to policy makers, education professionals, and students.